Formation mechanism of large pockmarks in the subaqueous Yellow River Delta. Issue 6 (3rd July 2019) - Tian, Zhuangcai; Guo, Xiujun; Qiao, Luzheng; Yu, Le; Xu, Guohui; Liu, Tao
Abstract: We have identified large pockmarks in an area of approximately 0.3 km 2 in the subaqueous Yellow River Delta in the Chengdao Sea. Gas eruption channels not been identified in the sediment layers in this area, and the formation mechanism of these large pockmarks remains unknown. To study the formation mechanism of these large pockmarks, we constructed a layered silty sediment model composed of appropriate geological materials. Then, we calculated the stress, displacement, and excess pore pressure in the layered silty sediment from the surface to a depth of 10 m using the Biot theory. A comparative analysis of the calculated results and the data measured in the field was then performed. Based on these results, we established a new formation mechanism for the large pockmarks. With the occurrence of storm waves, two extreme areas of displacement and excess pore pressure appeared in the layered silty sediment. These extreme values increased quickly in the seabed during the continuous action of storm waves. When the excess pore pressure surpassed the effective stress, the top silty layer instantly liquefied and then reconsolidated. Then, when the pore pressure of the interface position exceeded the effective stress produced by the overlying sediment, the sediments experienced "sand boil" damage. With the repeated action of strong waves, the boundary of the pockmark continued to expand, forming a large and stable pockmark. This work is of great value for further understanding and mitigating marine geologic hazards, such as coastal erosion, silt deposition, and unstable sediment, in the subaqueous Yellow River Delta.